2015
DOI: 10.1038/srep09982
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac salt is a newly discovered DDX3 inhibitor to treat oral cancer

Abstract: DDX3 belongs to DEAD box RNA helicase family and is involved in the progression of several types of cancer. In this work, we employed a High Throughput Virtual screening approach to identify bioactive compounds against DDX3 from ZINC natural database. Ketorolac salt was selected based on its binding free energy less than or equals to −5 Kcal/mol with reference to existing synthetic DDX3 inhibitors and strong hydrogen bond interactions as similar to crystallized DDX3 protein (2I4I). The anti-cancer activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…Moreover, DDX3 interacts and/or colocalizes with eIF4F components (Lai et al, 2008;Soto-Rifo et al, 2012). DDX3/Ded1p may facilitate RNA unwinding during ribosomal scanning of mRNAs or induce local separation of structured regions to facilitate cap recognition and eIF4A-catalyzed unwinding (Marsden et al, 2006;Lai et al, 2008;Soto-Rifo et al, 2012). We previously determined a DDX3-responsive region in the Rac1 5Ј UTR that contains two extended RNA duplexes (Chen et al, 2015), and in our present study we found that this structural feature exists in the 5Ј UTR of Prkaca (Fig.…”
Section: Ddx3 Promotes Translation Via Structured 5 Utr Elementsmentioning
confidence: 99%
“…Moreover, DDX3 interacts and/or colocalizes with eIF4F components (Lai et al, 2008;Soto-Rifo et al, 2012). DDX3/Ded1p may facilitate RNA unwinding during ribosomal scanning of mRNAs or induce local separation of structured regions to facilitate cap recognition and eIF4A-catalyzed unwinding (Marsden et al, 2006;Lai et al, 2008;Soto-Rifo et al, 2012). We previously determined a DDX3-responsive region in the Rac1 5Ј UTR that contains two extended RNA duplexes (Chen et al, 2015), and in our present study we found that this structural feature exists in the 5Ј UTR of Prkaca (Fig.…”
Section: Ddx3 Promotes Translation Via Structured 5 Utr Elementsmentioning
confidence: 99%
“…Several inhibitors of the ATPase activity of DDX3 have been recently identified (29)(30)(31)(32)(33)(34); however, an ATP-mimetic compound may have a low degree of selectivity in vivo because of the possibility of interacting with many targets (35).…”
mentioning
confidence: 99%
“…Furthermore, despite the characterization of several DEAD/DEAH proteins, few specific inhibitors targeting these ATP-dependent helicases have been developed. Several lines of evidence from earlier studies demonstrate that RNA helicase inhibitors are promising cancer drugs for the future (34,35). Clearly, the diversity of DEAD/DEAH helicases in promoting cancer development warrants a broader evaluation of this protein family and the rational design of their inhibitors.…”
Section: Discussionmentioning
confidence: 99%